The Effectiveness of Learning Management System in Bridging Curricular Lapses Among the Selected 3rd Year BSED Students at Bestlink College in the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
LMS or Learning Management System are software or web-based technology used toorganize, carry out, and evaluate a learning process. This research study focuses on theinterrelationship of the LMS and how it can be of great importance in bridging curricularlapses.This research found that learning management systems are an effective alternative forcontinuous learning and knowledge acquisition. LMSs serve as a bridge to connect manylapses, hindrances and lacks in the education sector and can be developed according tofeedback from students and teachers. LMSs are tools for producing, managing, anddistributing learning resources and are used by educational institutions and organizations todeliver hassle-free and smooth learning experiences. The study established frameworkguidelines for developing an effective LMS to further improve the quality of the content,providing more relevant materials, and adding reliable material resources.The implementation of the Learning Management System at Bestlink College of thePhilippines posits several concepts and ideas that have been defined for the betterment andcontinuous enhancement of the platform. To identify these constraints, it is important toconsider not only the things that need to be improved but also the ways to improve them. Theadministrators, teaching staff, developers, and learners are the key players in improving theLMS, and they must collaborate with one another and foster the exchange of feedback toachieve a great cause.
Keywords: Educational Management